APPLICATION OF TRADITIONAL MUSIC NUSANTARA EQUIPMENT USING MACROMEDIA FLASHacromedia Flash 8 - Yusup Wijayanto (Jurnal Sistem Informasi, 2008)
This writing explains information about a wide range of traditional musical instruments in Indonesia. The presentation was made in the form of applications using Macromedia Flash 8. It is intended that this application can be used as learning materials and can facilitate students in school to learn more about musical instruments of traditional archipelago